Applications of Ultrasound-Mediated Drug Delivery and Gene Therapy - Juliana Sitta (MDPI AG, 2021)
Gene therapy has continuously evolved throughout the years since its first proposal to develop more specific and effective transfection, capable of treating a myriad of health conditions. Viral vectors are some of the most common and most efficient vehicles for gene transfer. However, the safe and effective delivery of gene therapy remains a major obstacle. Ultrasound contrast agents in the form of microbubbles have provided a unique solution to fulfill the need to shield the vectors from the host immune system and the need for site specific targeted therapy. Since the discovery of the biophysical and biological effects of microbubble sonification, multiple developments have been made to enhance its applicability in targeted drug delivery. The concurrent development of viral vectors and recent research on dual vector strategies have shown promising results. This review will explore the mechanisms and recent advancements in the knowledge of ultrasound-mediated microbubbles in targeting gene and drug therapy.